Efektivitas Penggunaan Nirs Bundle dan Double Skin Barrier Hydrocolloid terhadap Penurunan Nasal Injury pada Bayi Prematur dengan NCPAP - Sakti Rahayu; Yulis Setiya Dewi; Agus Santoso Budi (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the effectiveness of using the NIRS Bundle and Double Skin Barrier Hydrocolloid to reduce nasal injury in premature infants using NCPAP. The method used is Quasy Experimental Design with Posttest-Only Control Design. The results showed that the p-value in the NIRS Bundle treatment group was p = 0.001 and p = 0.01 in the Double Hydrocolloid treatment. In conclusion, the NIRS Bundle intervention and the installation of Double Skin Barrier Hydrocolloid had a significant effect on reducing nasal injury in premature infants with NCPAP. Keywords: Hydrocolloid, Nasal Injury, NCPAP, Neonate, NIRS Bundle